Uncertainty due to infectious diseases and stock-bond correlation - Konstantinos Gkillas Gillas; Christoforos Konstantatos; Costas Siriopoulos (Econometrics, 2021)
We study the non-linear causal relation between uncertainty-due-to-infectious-diseases and stock-bond correlation. To this end, we use high-frequency 1-min data to compute daily realized measures of correlation and jumps, and then, we employ a nonlinear Granger causality test with the use of artificial neural networks so as to investigate the predictability of this type of uncertainty on realized stock-bond correlation and jumps. Our findings reveal that uncertainty-due-to-infectious-diseases has significant predictive value on the changes of the stock-bond relation.
Keywords: C45; C53; C58; G01; G11; 330; artificial neural networks; Granger causality test; infectious diseases; nonlinearity; stock-bond correlation; uncertainty